Evaluation of Two Different Strategies for Schistosomiasis Screening in High-Risk Groups in a Non-Endemic Setting - Luisa Roade; Elena Sulleiro; Cristina Bocanegra; Fernando Salvador; Begoña Treviño; Francesc Zarzuela; Lidia Goterris; Nuria Serre-Delcor; Inés Oliveira-Souto; Maria Luisa Aznar; Diana Pou; Adrián Sánchez-Montalvà; et al. (Tropical Medicine and Infectious Disease, 2023)
A consensus on the recommended screening algorithms for schistosomiasis in asymptomatic high-risk subjects in non-endemic areas is lacking. The objective of this study was to evaluate the real-life performance of direct microscopy and ELISA serology for schistosomiasis screening in a high-risk population in a non-endemic setting. A retrospective cohort study was conducted in two out-patient Tropical Medicine units in Barcelona (Spain) from 2014 to 2017. Asymptomatic adults arriving from the Sub-Saharan region were included. Schistosomiasis screening was conducted according to clinical practice following a different strategy in each setting: (A) feces and urine direct examination plus S. mansoni serology if non-explained eosinophilia was present and (B) S. mansoni serology plus uroparasitological examination as the second step in case of a positive serology. Demographic, clinical and laboratory features were collected. Schistosomiasis cases, clinical management and a 24 month follow-up were recorded for each group. Four-hundred forty individuals were included. The patients were mainly from West African countries. Fifty schistosomiasis cases were detected (11.5% group A vs. 4 % group B, p = 0.733). When both microscopic and serological techniques were performed, discordant results were recorded in 18.4% (16/88). Schistosomiasis cases were younger (p < 0.001) and presented eosinophilia and elevated IgE (p < 0.001) more frequently. Schistosomiasis is a frequent diagnosis among high-risk populations. Serology achieves a similar performance to direct diagnosis for the screening of schistosomiasis in a high-risk population.